Evaluating Perception of Undergraduate Medical Students About Integrated Modular System: Undergraduate Medical Students About Integrated Modular System - Fatima, Noor; Bani, Mehran Ullah; Rehman, Fazal Ur; Khan, Mansoor Ali Yazdan; Sultan, Mubeen; Mehsood, Nosheen; Ullah, Ubaid; Haq, Zia Ul (Pakistan Journal of Health Sciences, 2025)
The Integrated Modular System (IMS) is a structured program that begins with basic medical concepts and integrates all medical science components both horizontally and vertically. Objectives: To assess total perception scores, sub-variable scores, and the associations between research and demographic variables. Methods: An analytical cross-sectional study was conducted at Gomal Medical College using a quantitative approach with undergraduate students. Stratified random sampling was applied. The sampling frame comprised official enrollment lists from GMC’s registrar. Strata were defined by academic year (Year 1–Final Year) to ensure proportional representation. Within each stratum, students were randomly selected using Google Sheets’ RAND function to generate random numbers assigned to roll numbers. The top 40 unique random numbers per year were selected. A self-administered questionnaire, scored on a five-point Likert scale, assessed student perceptions across four sub-variables and three demographic variables. Scores were categorized as poor, fair, or good using Bloom’s criteria. SPSS version 27.0 was used to compute frequencies, percentages, and perform chi-square and Fisher’s exact tests. Results: Out of 200 participants, 72.5% had fair perception, 16.5% good, and 11.5% poor. No significant association was found between gender or residence and total perception score. However, a significant association existed between students’ year of study and their perception score. Conclusions: Students generally had an average yet cautiously positive perception of IMS, especially regarding learning behaviour and future outcomes. Concerns remain about achieving IMS goals and resource availability. DME should enhance evaluation guidelines and time allocation, while administration must improve self-directed learning resources